Peran Fasilitator dalam Meningkatkan Iman Umat melalui Kegiatan Katekese di Kbg. Sta Elisabeth Homa - Yuliana Dua Nukak; Skolastika Lelu; Petrus Tukan (CV. ALIM'SPUBLISHING, 2026)
This study entitled “The Role of Facilitators in Increasing the Faith of the People through Catechesis Activities at KBG Sta. Elisabeth Homa” aims to describe the implementation of catechetical activities, examine the role of facilitators, and identify the impact of these activities on the faith development of the community. This research employed a qualitative approach using a case study design. Data were collected through interviews and documentation involving facilitators, KBG administrators, and community members participating in catechetical activities. The data were analyzed through data reduction, data display, and conclusion drawing, while source triangulation and member checking were applied to ensure data validity. The findings reveal that catechetical activities are conducted through communal prayer, Scripture reading, material presentation, dialogue, faith sharing, and reflection. Facilitators serve as educators, motivators, faith companions, and facilitators of participation and dialogue. Their contextual and participatory approach helps community members understand Church teachings and apply them in daily life. The activities contribute positively to the development of faith, spirituality, ecclesial involvement, and social awareness among the participants. Therefore, the role of facilitators is essential in supporting the effectiveness of catechesis and strengthening the faith of the people in KBG Sta. Elisabeth Homa.